Unraveling Cochlear Dynamics: The Effect of Clicks, Tone Burst Frequencies, Polarity, and Stimulus Rates on Cochlear Microphonics in Individuals with Normal Hearing - Prajwal Kumar Eranna; Gowtham Varma; Animesh Barman (Journal of International Advanced Otology)
Background: Despite cochlear microphonic’s potential clinical application, especially in ANSD diagnosis, the optimal parameters to record cochlear microphonics and the effect of various stimulus parameters are not well understood yet, which makes its recording a difficult procedure. The present study was undertaken to determine the effect of stimulus polarity, rate, stimulus type, and stimulus frequency on different aspects of cochlear microphonics, which could help to decide an optimal stimulus parameter that can be used to record CM.